2015
DOI: 10.3329/seajph.v5i1.24844
|View full text |Cite
|
Sign up to set email alerts
|

Can we eliminate nutritional anaemia in the near future?

Abstract: not availableSouth East Asia Journal of Public Health Vol.5(1) 2015: 1-3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…This is may be due to the transition from feast to famine of iron store due to the rapid growth and expanding of blood volume during the first 2 years. As studies conducted in India [10], Nigeria [32] and Sub-Saharan Africa [4] showed, children within this age group require large amount of iron to maintain a near steady mean hemoglobin concentration within their body. Since the iron stores in their body has usually been depleted and exclusive breast feeding might not contain adequate iron, the initiation of complementary foods with high iron content is mandatory to satisfy their high iron demand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is may be due to the transition from feast to famine of iron store due to the rapid growth and expanding of blood volume during the first 2 years. As studies conducted in India [10], Nigeria [32] and Sub-Saharan Africa [4] showed, children within this age group require large amount of iron to maintain a near steady mean hemoglobin concentration within their body. Since the iron stores in their body has usually been depleted and exclusive breast feeding might not contain adequate iron, the initiation of complementary foods with high iron content is mandatory to satisfy their high iron demand.…”
Section: Discussionmentioning
confidence: 99%
“…It affects children both physically and mentally. As a result, working capacity and educational performance of children will be decreased [2, 4, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…It adversely affects the cognitive and physical development of children which in turn results in a significant impairment of work capacity and school educational performance ( 3 , 5-7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The possible reason for drop of prevalence anemia and/or improvement of hemoglobin level might be the about the consequences of anemia and the bene ts of iron on pregnant women and fetus health might have encouraged women to comply with the nutrition advices in reducing anemia. Iron-folic acid supplementation may have also contributed to the reduction the rate of anemia in the intervention group (33,34).…”
Section: Discussionmentioning
confidence: 99%